Greco-Roman wrestling on the world stage: performance trends and country comparisons - Latyshev, M.; Tropin, Y.; Pryimakov, O.; Curby, D.; Dokmanac, M.; Baic, M.; Korobeynikov, G.; Kerimov, F.; Khamidjonov, A.; Mirzolim, M. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2024)
Background. The Olympic Games represent the greatest sporting event, uniting athletes from around the world in the spirit of competition, achievement, and unity. The 2023 World Championship serves as the primary qualifier for the 2024 Olympic Games, providing critical data on the technical and strategic performance of elite wrestlers. Problem. The Study Aim is to identify key aspects of the best-ranked teams at the 2023 Greco-Roman Wrestling World Championship and to conduct a comparative analysis. Methods. This study analyzed 271 matches involving 86 wrestlers from 10 countries using the Performance Data Analysis platform by United World Wrestling. Key performance indicators such as match duration, number of actions in standing and parterre positions, and success indices were calculated. Results. Performance indicators revealed preferences for standing and parterre positions, with teams like Cuba and France scoring highest on the Most Successful Wrestler Index at 2.69 and 1.92, respectively. Notably, actions like gut wrench, step out, lifts, and take down represented over 70% of all actions. Statistical analysis confirmed significant differences in parterre actions among wrestlers from Azerbaijan, Turkey, Georgia, and Armenia. Conclusions. The study underscores the complexity of tactical preferences that influence team performance at world championships. The findings underscore the pivotal role of advanced analytics in enhancing understanding and strategic planning in competitive wrestling. The success index metrics, while associated with teams` rankings and Olympic qualification, do not fully capture the extent of their achievements.